ACCOUNTING STUDENTS' MOTIVATION for CHOOSING CAREERS as FORENSIC ACCOUNTANTS - Krisnhoe Rachmi Fitrijati (Jurnal Akuntansi, 2022)
This study aimed to investigate the internal and external factors that motivate accounting students to have a career as forensic accountants using Behavioral career decisions theory. Otherwise, this study analyses the motivation differences between students of public universities and private universities students. This study used a survey method by providing a questionnaire. The population in this study were active undergraduate accounting students at Jenderal Sudirman University, Muhammadiyah University of Purwokerto, and Wijayakusuma University. The respondents were 95, and data were analyzed using SPSS. The results show that internal and external motivation positively and significantly affect forensic accountants' career selection. There is no difference in motivation for choosing a forensic accountant career between accounting students in public universities and private universities in Banyumas Residency. The study results show achievements, recognition of appreciation, salary rewards and individual environmental conditions as motivational factors. With its unique characteristics as a particular field in accounting studies, forensics is one of the essential sciences in accounting. Therefore, accounting educators and academics can consider preparing a suitable forensic course syllabus or curriculum for the undergraduate programme.